2021
DOI: 10.3389/fonc.2021.706915
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Nine-lncRNA Risk Signature Correlates With Immunotherapy in Hepatocellular Carcinoma

Abstract: BackgroundHepatocellular carcinoma is one of the most common malignant tumors with a very high mortality rate. The emergence of immunotherapy has brought hope for the cure of hepatocellular carcinoma. Only a small number of patients respond to immune checkpoint inhibitors, and ferroptosis and tertiary lymphoid structure contribute to the increased response rate of immune checkpoint inhibitors; thus, we first need to identify those who are sensitive to immunotherapy and then develop different methods to improve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 51 publications
0
8
0
Order By: Relevance
“…Statistical analysis showed that this risk model has good robustness and predictive power and that it can independently predict OS in patients with HCC. Furthermore, the predictive accuracy of our signature surpassed that of the previously reported prediction signature of HCC dependent on FR-lncRNAs or FRGs (Liang et al, 2020;Chen et al, 2021;Liang Wang et al, 2021;Liang et al, 2021;Nie et al, 2021;Wan et al, 2021;Xu et al, 2021). The nomogram consisting of age, stage, and six FR-related lncRNA risk scores could be used to visually predict the OS of individual patients with HCC at 1, 3, and 5 years.…”
Section: Discussionmentioning
confidence: 64%
“…Statistical analysis showed that this risk model has good robustness and predictive power and that it can independently predict OS in patients with HCC. Furthermore, the predictive accuracy of our signature surpassed that of the previously reported prediction signature of HCC dependent on FR-lncRNAs or FRGs (Liang et al, 2020;Chen et al, 2021;Liang Wang et al, 2021;Liang et al, 2021;Nie et al, 2021;Wan et al, 2021;Xu et al, 2021). The nomogram consisting of age, stage, and six FR-related lncRNA risk scores could be used to visually predict the OS of individual patients with HCC at 1, 3, and 5 years.…”
Section: Discussionmentioning
confidence: 64%
“…For instance, lncRNA-ROR, a stress-responsive lncRNA highly expressed in HCC cells and enriched in extracellular vesicles derived from tumor cells, could induce primary chemoresistance by activating the TGF-β pathway in HCC (Takahashi et al, 2014). Moreover, immune-related lncRNA signatures have been reported as prognostic biomarkers and therapeutic targets in several tumors, including lung adenocarcinoma, bladder cancer, esophageal cancer, gastric cancer, rectal cancer, cervical cancer, and HCC (Chen et al, 2021;Lai et al, 2021;Liu et al, 2021;Nie et al, 2021;Pang et al, 2021;Song et al, 2021;Xing et al, 2021;Ye et al, 2021), indicating that immune-related lncRNAs could effectively be applied to determine the survival, prognosis, and treatment response. However, all these studies focused on excerpting the immune-related lncRNA profiles from the obtained immune-related genes based on co-expression analysis while ignoring the important role of the stromal components in tumor progression; immune-related genes remain inconclusive in different research studies, and there are no uniform criteria for filtering immune-related lncRNAs, which may limit the generalization of the predictive model.…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that the immune checkpoint related genes can effectively reflect the response rate of immune checkpoint inhibitors (ICIs), and immunophenoscore (IPS) associated with the responds to ICIs ( 29 , 30 ). Thus, we further investigated the association of risk signature with immune-related genes and IPS.…”
Section: Methodsmentioning
confidence: 99%